Analisis Instrumen Kemampuan Pemecahan Masalah Fisika Pada Materi Kalor Menggunakan Pendekatan Model Rasch - Nur Aisyah Listiawan; Lina Aviyanti; Fitria Arifiyanti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Competence in solving problems is a fundamental aspect of physics learning, yet students frequently demonstrate insufficient mastery, especially concerning heat-related material. A key factor behind this issue is the lack of optimal instruments for assessing such competencies. This study aims to examine the quality of an assessment instrument developed to measure problem-solving competence on heat topics. Using a descriptive quantitative approach, the study involved 51 eleventh-grade students from a state senior high school in Bandung. Twenty-five essay-type questions were administered and analyzed through Winsteps software applying the Rasch Model framework. Findings confirmed that the instrument satisfied validity and unidimensionality requirements, supported by a raw variance explained by measures reaching 51% and unexplained variance across contrasts 1–5 at 13.7%. Item validity was verified through MNSQ, ZSTD, and Point Measure Correlation assessments. Reliability analysis yielded strong outcomes across person reliability, item reliability, and Cronbach's Alpha. The instrument successfully distinguished students across different ability levels through a well-distributed range of item difficulties. However, discrimination analysis indicated that certain items need refinement to further improve instrument quality.